Using Stakeholder Perceptions to Inform Future Efforts to Implement Mental Health First Aid Training in China: A Qualitative Study - Lu, Shurong; He, Yanling; Searle, Kendall; Absetz, Pilvikki; Oldenburg, Brian; Reavley, Nicola (Frontiers in Psychiatry, 2021)
Background: The Mental Health First Aid (MHFA) training program has been widely implemented in many high-income countries. Evidence on the adaptation of this and other similar programs in resource-constrained settings like China is very limited. This study aimed to explore the views of key stakeholders on the implementation issues and contextual factors relevant to the scale-up of MHFA in China. Methods: Informed by the Consolidated Framework for Implementation Research, five implementation domains of intervention characteristics, characteristics of individuals, contextual adaptation, outer and inner setting, and implementation process were investigated through semi-structured in-depth interviews. Twenty-four stakeholders with diverse expertise in the Chinese mental health system were interviewed. Transcripts were coded using NVivo 12 software and thematically analyzed. Results: Fifteen themes and 52 sub-themes were identified in relation to the five domains. Participants saw MHFA as meeting the need for more evidence-based interventions to improve population mental health. Previous participants in MHFA training were satisfied with the course, but their intentions to help and levels of self-efficacy varied. Contextual adaptation of course content, delivery formats, and financing models, was seen as essential. External health policies and some socioeconomic factors (e.g., improved living conditions) were perceived as potential enablers of scalability. Low levels of engagement in health interventions and lack of supportive social norms were identified as potential barriers while executive support, quality control, and sustainable funding were viewed as facilitators of implementation. Conclusion: MHFA training meets some very important current societal and public health needs in China. To achieve its potential impact, significant contextual adaptation is required, particularly in terms of course content, delivery formats, and financing models. Overcoming low levels of engagement in community-based mental health interventions and combating stigma will also be critical for its scale-up.